The Altar Not Destroyed in Deuteronomy 16.21 - Bautch, Richard J. (Journal for the study of the Old Testament, 2016)
Deuteronomy 16.21–17.1 articulates three cultic laws establishing norms for worship. Interacting with recent Pentateuchal scholarship, this study examines Deut. 16.21–17.1 with an eye to issues in the text. An initial observation is that the literary unit does not cohere well with the surrounding laws in Deuteronomy. To address the problem of context, the study extends to comparable cultic laws elsewhere in Deuteronomy and in Exodus (Exod. 34.13; Deut. 7.5; 12.2–3). The comparison sheds greater light on Deut. 16.21–17.1 and suggests a dating of the text to the middle of the Second Temple period. Such dating, in turn, explains why this literary unit fits uneasily into its context of Deut. 16.18–18.22. The conclusion focuses on the altar in Deut. 16.21 as a reflection of changing perspectives on cultic worship expressed within the book of Deuteronomy.